Besifloxacin: Efficacy and Safety in Treatment and Prevention of Ocular Bacterial Infections. Issue 1 (June 2016) - Mah, Francis; Sanfilippo, Christine
Abstract This comprehensive review summarizes the mechanism of action, pharmacokinetics, efficacy, and safety of besifloxacin ophthalmic suspension, 0.6% and examines its role in the treatment of ocular surface bacterial infections. Besifloxacin possesses balanced activity against bacterial topoisomerase II (also called DNA gyrase) and topoisomerase IV. It has shown a low potential to select for bacterial resistance in vitro and demonstrated strong in vitro activity against many Gram-positive, Gram-negative, and anaerobic organisms, including methicillin-resistantStaphylococcus aureus andStaphylococcus epidermidis (MRSA and MRSE, respectively). Ocular pharmacokinetic studies have shown that besifloxacin achieves high, sustained concentrations in the tear fluid and conjunctiva following topical administration, with negligible systemic exposure. Large randomized, controlled clinical trials have established the efficacy and safety of besifloxacin administered three times daily for 5 days for treatment of acute bacterial conjunctivitis in both adults and children, with high rates of clinical resolution (up to more than 70% by day 5) and bacterial eradication (more than 90% by day 5), and a low incidence of adverse events. Additionally, besifloxacin applied twice daily for 3 days demonstrated greater efficacy than vehicle in treating bacterial conjunctivitis. Case reports, a large retrospective chart review, and animal studies have provided supporting evidence for the efficacy of besifloxacin in the management of acute bacterial keratitis. There is some evidence to suggest that besifloxacin may provide an advantage over other current-generation fluoroquinolones in antimicrobial prophylaxis for ocular surgery. Besifloxacin is an appropriate option for treatment of bacterial conjunctivitis, and its use in the treatment of bacterial keratitis and lid disorders, as well as for surgical prophylaxis, appears promising and warrants further evaluation.